HUMAN RELATION DALAM PERSPEKTIF ISLAM - Zuchairini, Andi (Hunafa: Jurnal Studia Islamika, 2008)
Human relation in a contemporary management, which places human beings in a proportional position, is so important that it should be paid serious attention. In Islamic perspective, human relation also emphasizes human beings as the most honored creatures who have various rights and obligations which must be complied with and respected. Its ultimate goal is to create the spirit of Islamic fraternity. However, this Islamic concept of human relation has not been translated yet into practice until these days.Kata Kunci: human relation, manajemen organisasi, interaksi sosial, ukhuwat islÃ¢miyah